Antisipasi Pada Keluhan Low Back Pain Dapat Mengurangi Kelelahan dan Meningkatkan Motivasi Kerja - Widana, I Ketut; Sumetri, Ni Wayan; Sutapa, I Ketut; Cahya Dewi, Gusti Ayu Oka (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 6 No 1 (2020): Volume 6 No 1 Juni 2020DO - 10.24843/JEI.2020.v06.i01.p09, 2020)
Low back pain has become a central issue of physiological health. Almost all the discussion of musculo skeletal complaints places more emphasis on the need to pay attention to the importance of health in the lower back. One of the causes of workers' complaints on the lower back is a less natural posture when on the move. The impact that is most easily observed as a result of the emergence of low back pain is the emergence of fatigue and decreased work motivation. Observation of the impact of low back pain on workers was examined using the same subject design . The subject are 11 people who work as wood carving artists. In period 1 the subjects worked in conventional working conditions, while in period 2 the subjects were given treatment, namely anticipation of complaints of low back pain, working in ergo-anthropometric working conditions, ie given ergonomic work tables and chairs with additional nutrition intake, active rest and work uniform. The fatigue variable was measured using a 30 items rating scale questionnaire and crafters' motivation was measured by a questionnaire on 4 Likert scales. Data analysis begins with descriptive analysis and normality test data with ShapiroWilk. Data with normal distribution are used t-paired analysis and data with abnormal distribution use Wilcoxon test. In this study it was found that ergo-anthropometric working conditions can reduce fatigue by 27.34% and increase work motivation by 20.39%. It can be concluded that efforts to anticipate complaints of low back pain can reduce fatigue and maintain work motivation of carving craftsmen.